2015
DOI: 10.3238/arztebl.2015.0489
|View full text |Cite
|
Sign up to set email alerts
|

Indications for and Risks of Elective Cesarean Section

Abstract: Scientific advances, social and cultural changes, and medicolegal considerations seem to be the main reasons for the increased acceptibility of cesarean sections. Cesarean section is, however, associated with increased risks to both mother and child. It should only be performed when it is clearly advantageous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
299
2
25

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(332 citation statements)
references
References 143 publications
6
299
2
25
Order By: Relevance
“…36 In present study, the morbidity rate was found as 12.02%. Surgical site infection (4.35%) was the commonest complication followed by atonic PPH (2.43%).…”
Section: Maternal Morbidities and Mortalitiesmentioning
confidence: 68%
“…36 In present study, the morbidity rate was found as 12.02%. Surgical site infection (4.35%) was the commonest complication followed by atonic PPH (2.43%).…”
Section: Maternal Morbidities and Mortalitiesmentioning
confidence: 68%
“…36 In our study, the morbidity rate was found as 11.60%. Surgical site infection (4.40%) was the commonest complication followed by atonic PPH (3.01%).…”
Section: Maternal Morbidities and Mortalitiesmentioning
confidence: 73%
“…[17][18][19][20] Mylonas et al states that the anxiety of vaginal delivery which is called as Tocophobia also plays a major role in increasing number of elective LSCS. 21 In present study 14 (12.2%) at 38 weeks and 16 (17.0%) patients had thinned out lower uterine segment. This was not statistically significant.…”
Section: Discussionmentioning
confidence: 74%
“…That is 0.1% and 0.09% in 38 weeks and 39 weeks respectively.10Hourani et al, Bakr et al and Okeke et al in their study observed that the risk of low APGAR score decrease with increase in gestational age. [20][21][22][23] Wilmink et al states that only after 40 weeks the APGAR score is 100% good <40 weeks babies had minor risk of low APGAR score which was not statistically significant. 16 In the present study 0.9 % at 38 weeks and 2.1% at 39 weeks babies had respiratory distress syndrome out of 209 women who underwent elective LSCS.…”
Section: Discussionmentioning
confidence: 99%